Improved metabolic profile after switch to darunavir/ritonavir in HIV positive patients previously on protease inhibitor therapy. Issue 5 (18th March 2013) - Ucciferri, Claudio; Falasca, Katia; Vignale, Francesca; Di Nicola, Marta; Pizzigallo, Eligio; Vecchiet, Jacopo
Abstract Metabolic abnormalities associated with cumulative exposure to antiretroviral therapy have been linked to an increased risk of myocardial infarction in HIV positive individuals. The aim of this study was to evaluate whether the switch from lopinavir/ritonavir (LPV/r) or fosamprenavir/ritonavir (FPV/r) to darunavir/ritonavir (DRV/r) is able to improve the lipid profile. A total of 13 Caucasian subjects (7 from LPV/r and 6 from FPV/r) were enrolled in the study and received DRV/r at the dose of 800/100 mg, without change in their NRTI backbone. Viro‐immunological parameters, triglycerides (TGs), total cholesterol (TCh), high‐density lipoprotein (HDL) and low‐density lipoprotein (LDL) cholesterol, fasting glucose, HOMA‐IR, indexes of hepatic and renal functionality, microalbuminuria and cystatin C were measured at baseline (T0), 3 months (T3), 6 months (T6), and 12 months (T12). The switch to DRV/r reduced levels of TCh, LDL, and TGs at T3. Similar improvements were confirmed further at T6 and at T12. A 14% increase in CD4+ count cells (P < 0.05) was observed. Serum cystatin C values showed a statistically significant decrease. After 12 months of switching to DRV/r from LPV/r or FPV/r, patients infected with HIV with TGs above 200 mg/dl, showed a 49% decrease in TGs, along with a 16% reduction of LDL and 19% reduction of TCh. Switching to DRV/r also improved immunological parameters, such as CD4+ cells count and cystatin C plasmatic levels, which may translate into a reduction of the cardiovascular risk. In conclusion, a switch to DRV/r should be considered in those HIV positive patients undergoing antiretroviral therapy, who also present abnormal lipid profiles. J. Med. Virol. 85:755–759, 2013. © 2013 Wiley Periodicals, Inc.